Strategi Koalisi Partai Politik Lokal Dan Partai Politik Nasional Dalam Pemenangan Pasangan Calon Kepala Daerah - Gunawan, Gunawan; Bainus, Arry; Paskarina, Caroline (Politea : Jurnal Politik Islam, 2020)
This study aims to describe, and analyze the coalition strategies of local political parties and national political parties in the framework of winning regional heads in a region that has built a political dynasty for a dozen years, especially in Nagan Raya District, Aceh Province. The theory used is the political strategy theory used by Schroder (2010) which assesses political strategy is a framework of steps or plans used in order to realize political ideals. The political strategy is divided into two: political offensive strategy and defensive political strategy. This study uses a qualitative method. The data source consists of primary and secondary data. Primary data were obtained from the results of in-depth interviews with a number of informants, while secondary data were obtained from literature review and related documents. The research instrument is the researcher himself. Research informants consisted of coalition leaders, bearers of political parties, couples who won in Nagan Raya regional elections, Jamin Idham and Chalidin. The results showed that the strategy adopted by the candidate pair Jamin Idhan and Chalidin (JADIN) to fight incumbents, namely Teuku Raja Keumangan and Said Junaidi (TRK ONLY) was an offensive strategy.